DEVELOPMENT OF AR-BASED CAREER INFORMATION SERVICE MEDIA AT SDN 07 TALA, TAKALAR DISTRICT - Husna, Asmaul; Harum, Akhmad; Aswar, Aswar (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Career information services at SDN 07 Tala still rely on oral explanations and simple posters, resulting in low understanding of sixth grade students regarding various professions, tasks, educational paths, and their relationship to personal interests and talents. This study aims to: (1) Describe the needs of Augmented Reality-based career information service media at SDN 07 Notes; (2) Develop a prototype for developing Augmented Reality-based career information service media at SDN 07 Note; (3) Measure the validity level of Augmented Reality-based career information service media at SDN 07 Note; and (4) Assess the practicality level of Augmented Reality-based career information service media at SDN 07 Tala. The study uses the Borg and Gall Research and Development (R&D) model approach, which was modified from 10 stages to 8 stages, including initial research, design, prototype development, expert validation, revision, small group trials, and the final product. The results of this study are (1) The need for AR media is very urgent (average career understanding score 66-75%); (2) The prototype developed systematically from 6 to 9 professions with a complete menu; (3) Very reasonable validity (99.58%); and (4) Practical practicality (95.05%) based on teacher (97.50%) and student (92.60%) responses. The conclusion confirms that AR-based Lingkar media is effective in increasing elementary school students' career insights in an interactive and fun way, recommended for routine integration in BK services with the addition of audio narration and local professions.